Biosynthesis and in-vitro characterizations of copper oxide nanoparticle using Mangifera indica seed kernel extract and assessment of pharmacological properties - Pranay Pramanik; Krishnendu Dakua; Trisha Kar; Ranabir Sahu; Tarun Kumar Dua; Gouranga Nandi; Sangita Dey; Anoop Kumar; Ritu Khanra; Paramita Paul (Hybrid Advances)
The production of metal nanoparticles is an expanding field of study owing to its promise in advancing technologies. Typically, these nanoparticles are created through chemical processes that are often detrimental to the environment. Globally large amounts of fruit waste are generated daily. Utilizing these fruit waste to create metal nanoparticles through environmentally friendly methods presents an innovative, cost-efficient, and eco-friendly approach compared to conventional techniques which are energy intensive, costly and hazardous for the environment. Mango seed kernel extract and copper sulphate pentahydrate were used to produce copper oxide nanoparticles (CONPs) using a green synthesis method. Physico-chemical characterizations of the CONPs were done by DLS, FTIR, UV–Visible spectrophotometry, SEM, TEM, EDX and X-ray diffraction. The nanoparticles showed surface plasmon resonance peak at 276 nm, and were found to be of size 211 nm. FTIR analysis inveterate the occurrence of phytochemicals in both the mango seed kernel extract as well as the nanoparticles, suggesting the kernel's potential as stabilizers, reducers, and capping agents. DPPH free radical scavenging assay indicated the CONPs to have mild antioxidant activity with IC50 of 453.72 μg/mL. The synthesised CONPs were found to successfully inhibit growth of both Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative) bacteria. Moreover, MTT assay exhibited strong anticancer potential of CONPs against SH-SY5Y neuroblastoma cell-lines with IC50 of 24.14 μg/mL.